2011
DOI: 10.1007/s11367-011-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

USEtox human exposure and toxicity factors for comparative assessment of toxic emissions in life cycle analysis: sensitivity to key chemical properties

Abstract: Purpose The aim of this paper is to provide science-based consensus and guidance for health effects modelling in comparative assessments based on human exposure and toxicity. This aim is achieved by (a) describing the USEtox™ exposure and toxicity models representing consensus and recommended modelling practice, (b) identifying key mechanisms influencing human exposure and toxicity effects of chemical emissions, (c) extending substance coverage. Methods The methods section of this paper contains a detailed doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
182
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 56 publications
0
182
0
2
Order By: Relevance
“…Additionally, in an LCA study containing several substances in the inventory, there is not only one type of non-cancer human toxicity effects covered. For example, the CF can reflect severe chronic damage to foetus development as well as temporary skin irritation (Rosenbaum et al 2011). For cancer human toxicity effects, the CF can likewise reflect different cancer causes including both substances that induce tumours and that increase their incidence.…”
Section: Best-estimate Approach For Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in an LCA study containing several substances in the inventory, there is not only one type of non-cancer human toxicity effects covered. For example, the CF can reflect severe chronic damage to foetus development as well as temporary skin irritation (Rosenbaum et al 2011). For cancer human toxicity effects, the CF can likewise reflect different cancer causes including both substances that induce tumours and that increase their incidence.…”
Section: Best-estimate Approach For Datamentioning
confidence: 99%
“…The models selected were ECOSAR (US EPA 2012) for ecotoxicity and QSAR Toolbox (OECD 2016a) for mammalian toxicity. To fill as many data gaps as possible, the acuteto-chronic extrapolation, as suggested by Rosenbaum et al (2011), was used as a complementary method to estimate cancer (if indicated to be mutagenic) and non-cancer ED 50 based on acute LC 50 values as predicted with the US EPA T.E.S.T. model (US EPA 2017).…”
Section: Evaluation Of Data Sources For Inclusion In the Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…USEtox is a consensus model developed within the Life Cycle Initiative led by the United Nations Environmental Program and the Society of Environmental Toxicology and Chemistry (UNEP-SETAC) (Hauschild et al, 2008;Henderson et al, 2011;Rosenbaum et al, 2008Rosenbaum et al, , 2011. This parsimonious and transparent model can screen thousands of chemicals and is widely used, but only provides continent-generic characterisation factors and impact scores for a generic unknown continent.…”
Section: Introductionmentioning
confidence: 99%
“…Humbert et al (2011) showed that intake fractions from inhalation of primary particulate matter can be modelled based on emission release height and "archetypal" environment (indoor versus outdoor; urban, rural, or remote locations) and vary by orders of magnitude among conditions considered. Several other authors have used the archetype approach to estimate human toxicity impacts from air emissions, including Hellweg et al (2009) and Wenger et al (2012) for indoor air and Rosenbaum et al (2011) for urban emissions by continent. However, a similar archetypal approach has not yet been developed for related fate and exposure for water emissions.…”
Section: Introductionmentioning
confidence: 99%